Combined PNF and myofascial release techniques impair acute strength performance: A randomized controlled cross-sectional study : Combined PNF and MFR techniques impair acute strength performance - Inacio, Pedro Augusto; dos Santos Rodrigues , Yuri; Magalhães Sales , Marcelo; Machado , Sérgio; Oliveira-Silva , Iransé; Pereira da Silva Rocha , Fernanda; Coelho Silva, Adriano; Caroline Rodrigues , Anne; das Aguas Caixeta, Davi; Roberto Barsanulfo Júnior, Silvio; Alves Silva, Weder; Albernaz , Thiago; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Numerous strategies can be implemented as preconditioning preparation to increase strength production, including PNF and MFR strategies, however there are still contradictions in the literature regarding competing effects between preconditioning actions and strength perfor-mance, which it becomes plausible to look for the impact is effect on strength resistance perfor-mance. Objective: of the study was to evaluate the acute effects of series of PNF, myofascial release (MFR), or the sum of the methods, on the development of resistance strength in subsequent series of deadlifts. Methods: Eight adults of both sexes (25.4 ± 4.1 years) participated in the study, attend-ing the gym on 7 visits. The first visit consisted of a sample characterization. On the second and third visits, participants performed the maximum repetition Deadlift procedure, from the fourth to seventh visits, they were randomly divided into: a) CTL; b) PNF; c) MFR; d) PNF + MFR. All sessions followed three sets of the Deadlift exercise with 80% RM. Results: The repeated measures ANOVA showed significant differences between the control condition (no intervention) and the PNF inter-vention (p = 0.034) and MFR + PNF (p = 0.047). However, the Control vs. MFR there were no signif-icant differences (p = 0.07), as well as PNF vs. MFR (p = 0.585), and PNF vs. PNF+MFR (p = 0.382). Conclusion: Strength performance was influenced by the PNF method, or associated with MFR, both reducing total work.